"An integrated clip-shaped costal cartilage carving approach for rhinoplasty". Issue 8 (August 2022) - Lin, Yanyan; Chen, Ben; Zhu, Xiuying; Ma, Yingjie; Liu, Jia; Wang, Min; Chen, Xi
Summary: Background: Nasal tip management is considered to be one of the most complicated and challenging parts of rhinoplasty in East Asian patients. Within current rhinoplasty surgical practice, costal cartilage serves as an ideal source for grafting due to its ability to provide strong support to the nasal tip. Methods: From March 2013 to December 2021, integrated clip-shaped costal cartilage grafts were applied to patients with primary ( n  = 12) or secondary ( n  = 3) short nose deformities. The costal cartilage was carved into an monobloc clip-shaped cartilage graft and then placed on the nasal septum and fixed with sutures. The nasal length index, projection index, and nasolabial angles were measured preoperatively and postoperatively. Postoperative evaluation at 8 months was performed using a grading scale. Results: A total of 15 patients were included in this study with an average age of 23.7 ± 3.6 years. The mean follow-up period was 14.3 ± 5.3 months and ranged from 8 to 26 months. There were statistically significant differences between the preoperative and postoperative values in nose length index and projection index. Also, the nasolabial angle was significantly reduced. Postoperative evaluation, conducted at a minimum of 8 months following surgery, showed that 86.6% (13/15) of patients felt that their surgical results were good or excellent. No patients rated the results as "poor". Conclusion: The integrated clip-shaped costal cartilage carving approach has been shown to be a practical method of obtaining satisfactory esthetic outcomes in patients with nasal deformities.